Diameter Effect on the Wall Temperature Behaviors During Supercritical Water Heat Transfer Deterioration in Circular Tubes and Annular Channels - Cheng, Hui; Yanlin, Aaron Bai; Wang, Jun; Zhao, Jiyun (Frontiers in Energy Research, 2019)
Diameter effect on heat transfer deterioration (HTD) for supercritical water upward flow in circular tubes and annular channels at low mass flux and high heat flux was studied numerically based on validated turbulence model. When the same boundary conditions were applied, i.e., mass flux, heat flux, and inlet temperature, it was observed that for circular tubes the first peak of wall temperature moves upstream and its magnitude increases at first then decreases as tube diameter increases, the second peak moves downstream as tube diameter increases. For annular channels with a fixed inner diameter, HTD is suppressed with small outer diameter, while HTD occurs gradually as outer diameter increases. The phenomenon agrees with previous experiment studies. The mechanism was analyzed based on fully developed turbulent velocity profiles at the heated sections inlet. Increasing inner diameter for circular tubes or outer diameter for annular channels will result in the decrease of maximum velocity and velocity gradient in the near heated wall region, which makes velocity profile in this region much easier to be flattened by the buoyancy. Then an M-shaped axial velocity profile is formed, which will significantly decrease the Reynolds shear stress and the turbulent kinetic energy and hence impair the heat transfer and cause HTD. At the same flow conditions, HTD is much easier to occur in circular tubes than in annular channels with the same hydraulic diameters.